Assessment of the role of a leader in shaping sustainable organizational culture - Dalia Štreimikienė; Asta Mikalauskiene; Lina Digriene; Grigorios L. Kyriakopoulos (Amfiteatru Economic Journal, 2021)
The sustainable organization culture is one of the most important intangible assets and driver of competitiveness of organizations. The aim of this article is to reveal the role of various form of leadership in shaping organisational culture by conducting empirical study in the network of pharmaceutical companies distinguished with high share of young females working in such companies in Lithuania. This is very competitive sector and has important implications on public health and other sustainability issues therefore this area was selected for the empirical study on testing leadership impacts. The main focus of the study is leader's personal features and their impact on team work and relationships with clients, what effect male and female managers have on innovation culture in the network of pharmaceutical companies and what impact leader's characteristics have on sustainable of organizational culture and long-term development goals of the company. The study results showed that transformational leadership can provide for more effective organisational culture than transactional leader, because such a leader is oriented towards the transformation of employee expectations and can create more opportunities for sustainable organizational culture.
Keywords: O10; D23; M14; 330; leadership; sustainability; organizational culture; pharmaceutical companies